Mentoring, Social Capital, and Human Capital : Mentoring, Sozialkapital und Humankapital - Hamilton, Stephen F. [Verfasser]; Hamilton, Mary Agnes [Verfasser] (My University, 2014)
"The transition from school to work is an important component of the life-stage from adolescende to adulthood. This issue's focus on school and work is central to besoming adult baucuse, unlike prior lif-stage transitions, the transition to adulthood is defined primarily by changes in the roles people perform in social institutions rather than by physiological changes. Ceasing to be a full-time pupil or student and assuming full-time employment are critical markers of adult status. Employment enables financial an residential independence of parents, and potentially the establisment of a new nuclear family, and full engagement in civil society, additorial role changes that are critical markers of adulthood." (Autorenreferat, BIBB-Doku)

"Der Übergang von der Schule in die Arbeitswelt bildet einen bedeutenden Abschnitt im Übergang von der Adoleszenz in das Erwachsenenleben. Dieser Übergang in die Erwachsenenwelt ist überwiegend durch den Rollenwechsel bestimmt, den die Individuen in sozialen Institutionen erfahren, und weniger durch physiologische Veränderungen. Die Aufgabe der Rolle, Berufsschüler/in oder Student/in zu sein und eine Vollzeitbeschäftigung auszuüben, sind entscheidende Merkmale des Erwachsenenalters. Eine Beschäftigung ermöglicht eine Unabhängigkeit von den Eltern und gewährt die Chance, eine eigene Familie zu gründen und sich voll sozial und politisch zu engagieren." (Autorenreferat)
Keywords: T 4.5 Soziologie; G 1.3.2.2 Übergänge; P 1.1 Jugendliche; P 3.1.3 Coaches, Supervisoren, Moderatoren; Berufseinmündung; Jugendlicher; Adoleszenz; Rollenwandel; Mentoring; USA; Bundesrepublik Deutschland